2009
DOI: 10.1038/sc.2009.43
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of depression, anxiety and stress in persons with traumatic and non-traumatic post-acute spinal cord injury

Abstract: This study examined multiple mental health outcomes after NT-SCI in Australia. This study provides some evidence that the results of studies of depression, anxiety or stress in persons with T-SCI can be generalised to those with NT-SCI in the post-acute phase. NT-SCI patients are also at substantial risk of poor mental health outcomes. General demographic and injury-related characteristics do not seem to be important factors associated with the mental health of adults with SCI whether the SCI is traumatic or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
6
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 18 publications
4
41
6
2
Order By: Relevance
“…53 Co-occurring symptoms and psychiatric conditions should also be considered in future research. Migliorini et al [30][31][32][33] did provide these data and found that 29% of their sample reported clinical symptoms of anxiety, along with depression and general distress. Similarly, Craig et al [23] identified GAD comorbidities (e.g.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…53 Co-occurring symptoms and psychiatric conditions should also be considered in future research. Migliorini et al [30][31][32][33] did provide these data and found that 29% of their sample reported clinical symptoms of anxiety, along with depression and general distress. Similarly, Craig et al [23] identified GAD comorbidities (e.g.…”
Section: Discussionmentioning
confidence: 93%
“…As data used for a meta-analysis should be sourced from independent samples, the studies were also checked so that there was no overlap in the samples utilised. 42 Six studies 25,[30][31][32][33][34] were subsequently pooled into two studies. Specifically, only the study providing the largest sample size was included.…”
Section: Eligibility Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, research has found the aetiology of SCI to have little or no effect on individuals' psychological well-being, in relation to anxiety, depression, stress and quality of life, 16,17 and researchers have even suggested no apparent differences in post-traumatic stress disorder. 18 These results, therefore, suggest that a similar approach to aiding patients' psychological wellbeing in rehabilitation settings would be effective in both individuals with traumatic and non-traumatic injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Depression and anxiety in the spinal cord injury population have prevalence rates of 21-37% and 19-29%, respectively, and these conditions have been positively associated with SHCs, health care utilization and more frequent use of prescription medications. [20][21][22][23] The prevalence of major depressive disorder in the pediatric-onset SCI population has been reported to be significantly lower compared with that of the adult-onset SCI, as well as the general population; 24,25 however, given the fact that antidepressants were the fifth most common routine medication, close follow-up of mental health is warranted over time, especially in relation to development of SHCs. 24,25 The increased risk of peptic ulcers and gastroesophageal reflux disease is well documented in SCI and has been attributed to unopposed vagal stimulation, decreased mucosal perfusion and persistent supine position.…”
Section: Discussionmentioning
confidence: 99%